Differentiation of strains from the Bacillus cereus group by RFLP‐PFGE genomic fingerprinting. Issue 20 (25th September 2013) - Otlewska, Anna; Oltuszak‐Walczak, Elzbieta; Walczak, Piotr
<x xml:space="preserve">Abstract</x> Bacillus mycoides, Bacillus pseudomycoides, Bacillus weihenstephanensis, Bacillus anthracis, Bacillus thuringiensis, and Bacillus cereus belong to the B. cereus group. The last three species are characterized by different phenotype features and pathogenicity spectrum, but it has been shown that these species are genetically closely related. The macrorestriction analysis of the genomic DNA with the NotI enzyme was used to generate polymorphism of restriction profiles for 39 food‐borne isolates (B. cereus, B. mycoides) and seven reference strains (B. mycoides, B. thuringiensis, B. weihenstephanensis, and B. cereus). The PFGE method was applied to differentiate the examined strains of the B. cereus group. On the basis of the unweighted pair group method with the arithmetic mean method and Dice coefficient, the strains were divided into five clusters (types A–E), and the most numerous group was group A (25 strains). A total of 21 distinct pulsotypes were observed. The RFLP‐PFGE analysis was successfully used for the differentiation and characterization of B. cereus and B. mycoides strains isolated from different food products.